MEDIA MASSA DAN REPRESENTASI PEREMPUAN DALAM IKLAN - Anhar Fazri; dini hartati (SOURCE : Jurnal Ilmu Komunikasi, 2018)
Mass media is a container of creativity with various functions and roles that exist within it, andof course with attention to the discussion and journalistic ethics. So also with the role displayedby women in the mass media, especially advertising. Advertising is part of promoting goods orother products, including using women as a tool to beautify the uniqueness of the woman.Women are considered a product that is easy to sell or serve as a business land for mediaowners, so it represents women only to sell their bodies and beauties. That way, ads featuringwomen as objects are sold as if sexual displays are invisible and women only play a role in thehousehold sphere only. While the concept of Islam is very clear about glorifying women, andwomen have the highest degree. Therefore, the role raised today is much to harass women.Keywords : Mass Media, Representation, Advertisement, Women